Hazardous Solid Waste Management in Universitas Diponegoro: Planning Towards Environmental Sustainability - Sri Sumiyati; Bimastyaji Surya Ramadan; Mochamad Arief Budihardjo; Aufa Rahma Al-Hafidz; Haekal Awliya Muhammad Salman; Rizal Adi Wirawan (Universitas Diponegoro, 2022)
Universitas Diponegoro has a role in contributing to considerable numbers of hazardous solid waste from academic activities as it is the largest university in Central Java Province, Indonesia. Therefore, improper hazardous solid waste will cause potential disease for humans and pollute the environment. For this reason, proper hazardous solid waste management is urgently needed. This research aims to design hazardous solid waste management for Universitas Diponegoro as a pilot testing study. The research used questionnaires, surveys, in-depth interviews, and observations to construct an appropriate hazardous waste management system. The result showed that hazardous solid waste in Universitas Diponegoro came from 5 sources: education, office, laboratory, supporting facilities, and Pleburan Campus. The estimation of hazardous solid waste produced by the Universitas Diponegoro in 2021 is as much as 100.4 kg/day. The hazardous waste characteristics are toxic, corrosive, flammable, and infectious. In the hazardous management planning that was developed, the design of the waste transportation and storage system at the waste station in the Tembalang and Pleburan campuses has a total investment and operation cost of Rp 6,259,841,999 for 10 years of operation. This design is hoped to enhance the campus's achievement in sustainability efforts.